Seed Priming Improves Seed Germination and Seedling Growth of Isatis indigotica Fort. under Salt Stress - Xu-Wen Jiang; Cheng-Ran Zhang; Wei-Hua Wang; Guang-Hai Xu; Hai-Yan Zhang (HortScience, 2020)
The effects of CaCl2, GA3, and H2O2 priming on Isatis indigotica Fort. seed germination characteristics, seedling growth parameters, and antioxidant enzyme activities under salt stress were investigated. NaCl had an adverse effect on the germination and seedling performance of I. indigotica. However, these three priming agents alleviated salt stress by increasing the germination percentage, improving seed vigor, accelerating germination velocity, and establishing strong seedlings. The optimal concentrations were 15 g/L for CaCl2, 0.2 g/L for GA3, and 40 mm for H2O2. Seed priming treatments enhanced the activities of antioxidant enzymes in seedlings, such as superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), under a salt environment, which reduced the oxidative injury caused by salt. Seed priming is a promising technique that can enhance the ability of I. indigotica seed germination when salt is present.